2018
DOI: 10.1111/dom.13476
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of empagliflozin‐based quadruple therapy compared with insulin glargine‐based therapy in patients with inadequately controlled type 2 diabetes: An observational study in clinical practice

Abstract: This open-label, prospective study evaluated the effectiveness and safety of empagliflozin as add-on therapy in inadequately controlled type 2 diabetes (T2D) patients (glycated haemoglobin [HbA1c], 7.5-12%) who were already using three other types of orally active antidiabetic agents. A total of 268 T2D patients were enrolled and divided into two groups, empagliflozin (EMPA 25 mg/d, n = 142) or insulin glargine (INS, n = 126), respectively. After the treatment period of 24 weeks, HbA1c and fasting plasma gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 13 publications
2
19
2
Order By: Relevance
“…Recently, several real-world data from clinical practice settings were reported which showed similar glucose-lowering efficacy of SGLT2 inhibitors as add-on therapy to those from previous RCTs and meta-analyses [131415]. These findings were consistently observed in Korean patients with T2DM [161718]. In actual clinical practice, it may also be considered to change an OAD to other class of OAD if glycemic goal is not achieved, which means switch therapy.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Recently, several real-world data from clinical practice settings were reported which showed similar glucose-lowering efficacy of SGLT2 inhibitors as add-on therapy to those from previous RCTs and meta-analyses [131415]. These findings were consistently observed in Korean patients with T2DM [161718]. In actual clinical practice, it may also be considered to change an OAD to other class of OAD if glycemic goal is not achieved, which means switch therapy.…”
Section: Introductionmentioning
confidence: 67%
“…There have been few real-world studies of SGLT2 inhibitors reported in Koreans. Previous two studies evaluated the efficacy and safety of dapagliflozin or empagliflozin-based quadruple therapy in Koreans [1718]. Another Korean study examined the efficacy of dapagliflozin and clinical characteristics of good responders to dapagliflozin [16].…”
Section: Discussionmentioning
confidence: 99%
“…Although the retrospective and observational nature of our study is a limitation, it has the advantage of reflecting the current state of T2D management in the real world. Although there have been a few studies on quadruple therapy in T2D, these studies focused on the effectiveness of SGLT2i-based quadruple regimen in patients with poorly controlled T2D and did not consider variable combinations of quadruple OHA therapies [7,8]. In addition, the major strength of our study was contributing additional evidence for recommendation or consideration of quadruple therapy for some patients in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a quadruple combination of OHAs targeting various organs could be a feasible option for patients with poorly controlled T2D. However, despite its potential, only limited data are available on the use of quadruple OHAs [7,8]. Therefore, the present study investigated the effectiveness of quadruple OHAs in Korean patients with T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the established efficacy of insulin, patients are not always willing to initiate and maintain strict adherence to the use of this treatment regimen [6][7][8]. The reluctance to initiate and adhere to insulin treatment by the patient and, in some cases, the prescribers may be attributed to an emerging phenomenon known as 'psychologic insulin resistance' (PIR) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%